Effect of Different Templates on the Synthesis of Mesoporous Sodalite - Shima Shirani Lapari; Zainab Ramli; Sugeng Triwahyono (Journal of Chemistry)
Sodalite is a type of zeolite having ultramicropore size and high thermal stability with strong basic sites. However, sodalite has several drawbacks in the catalyst application due to its smallest pore size (2.8 Å) and low surface area. To overcome these disadvantages, microporous sodalite can be modified to have mesoporous structure but maintain its active sites suitable for catalyst applications. This study was focused on the synthesis of mesoporous sodalite using various organic templates as structure directing molecules. A hierarchical mesoporous sodalite has been synthesized hydrothermally at 150°C for crystallization by using several mesotemplate and fumed silica as a silica source. The synthesized samples were characterized using XRD, FTIR, BET surface area, and FESEM. XRD and FTIR showed that all templates being used in the synthesis produced sodalite phase. The sodalite synthesized using organosilane (trimethoxysilyl-propyldimethyloctadecyl ammonium chloride) and mixture of tetrapropyl ammonium hydroxide and cetyltrimethylammonium bromide with ratio of 1 : 1 showed mesoporosity as proven by higher BET surface area as compared to microporous sodalite with different pore structure as proven by pore distribution.